2017
DOI: 10.1038/s41598-017-15710-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Propionibacterium acnes in the Retinal Granulomas in Patients with Ocular Sarcoidosis

Abstract: The etiology of sarcoidosis is still obscure; however, Mycobacteria and Propionibacterium acnes are considered the most implicated etiological agent for sarcoidosis. To investigate whether P. acnes is an etiological agent for sarcoid uveitis, we analyzed the frequency of P. acnes detected within the biopsied retinas from patients with ocular sarcoidosis by immunohistochemistry with a P. acnes-specific monoclonal antibody (PAB antibody). Eleven patients (12 eyes) with sarcoid uveitis were enrolled in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…It is well known for its involvement in the pathogenesis of acne vulgaris [19]; moreover, its role in various postoperative infections such as endocarditis, endophthalmitis, and central nervous system (CNS) infections has been reported [5]. In addition, P. acnes can invade and persist in epithelial cells and circulating macrophages in its intracellular latent form [5], which results in chronic inflammation such as sarcoidosis [6,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known for its involvement in the pathogenesis of acne vulgaris [19]; moreover, its role in various postoperative infections such as endocarditis, endophthalmitis, and central nervous system (CNS) infections has been reported [5]. In addition, P. acnes can invade and persist in epithelial cells and circulating macrophages in its intracellular latent form [5], which results in chronic inflammation such as sarcoidosis [6,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies increasingly suggest that the immunopathogenesis of sarcoidosis is highly associated with environmental and acnes DNA were significantly higher in granulomatous areas than that in nongranulomatous areas in sarcoid lymph nodes [80]. Other studies have confirmed this finding [81],.…”
Section: Studies Regarding the Immunopathogenesis Of Sarcoidosismentioning
confidence: 94%
“…This microorganism is the only one that has been cultured from sarcoidosis lesions ( 58 , 59 ). Numerous studies have identified specific immune responses to Propionibacterium acnes in sarcoidosis patients but much less to none in non-sarcoidosis controls ( 52 , 60 , 61 ). Propionibacterium acnes was highly associated with sarcoidosis in a meta-analysis of studies evaluating infectious agents as a cause of the disease ( 47 ).…”
Section: Potential Infectious Causes Of Sarcoidosismentioning
confidence: 99%